Evaluation of soil extractants for silicon availability for sugarcane - Crusciol, Carlos Alexandre Costa [UNESP]; de Arruda, Dorival Pires [UNESP]; Fernandes, Adalton Mazetti [UNESP]; Antonangelo, João Arthur; Alleoni, Luís Reynaldo Ferracciú; Fernandes, Dirceu Maximino [UNESP]; McCray, James Mabry (Taylor & Francis, 2018)
Adequate evaluation and interpretation of silicon (Si) phytoavailability in soil is a key to fertilizer recommendation. This study was conducted to determine the effect of soil texture on the choice of Si extractant, and provide baseline data on the relationship between extractable Si and sugarcane Si accumulation. The effects of soil texture and extractant solutions of Si were investigated on soil of nine areas of sugarcane cultivation. Si contents in clayey soils were higher than in sandy soils only in the extraction with standard calcium chloride, acetic acid, potassium chloride (KCl), and sodium acetate buffer. Other extractants failed to reveal differences in the Si availability among the three soil textures. The choice of the extractant should consider soil texture for the determination of adequate Si contents in soils planted with sugarcane, and the extractants that proved to be more efficient in the three soil textures was acetic acid and KCl.
Keywords: clay; silicon uptake; soil solution; soil texture; sugarcane stalk yield